2010
DOI: 10.1080/02626667.2010.512867
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of data-driven modelling techniques for river flow forecasting

Abstract: Accurate forecasting of streamflow is essential for the efficient operation of water resources systems. The streamflow process is complex and highly nonlinear. Therefore, researchers try to devise alterative techniques to forecast streamflow with relative ease and reasonable accuracy, although traditional deterministic and conceptual models are available. The present work uses three data-driven techniques, namely artificial neural networks (ANN), genetic programming (GP) and model trees (MT) to forecast river … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…According to the statistics of RMSE and MAE, both methods performed equally well. Similar results have been reported about close performance of ANN and M5 models in rainfallrunoff modeling [43] and river flow forecasting [44]. The main advantage of M5 model tree is that it provides the results in a simple and comprehensible form of regression equations [1], which can be easily used in the calculation of ET .…”
Section: Resultssupporting
confidence: 67%
“…According to the statistics of RMSE and MAE, both methods performed equally well. Similar results have been reported about close performance of ANN and M5 models in rainfallrunoff modeling [43] and river flow forecasting [44]. The main advantage of M5 model tree is that it provides the results in a simple and comprehensible form of regression equations [1], which can be easily used in the calculation of ET .…”
Section: Resultssupporting
confidence: 67%
“…Thus Genetic Programming entered in rainfall-runoff modeling. It was also found that GP results were superior to that of M5 Model Trees another data driven modeling technique [12,13]. Apart from these two variables the use of GP for modeling for many hydraulic engineering processes was found necessary for similar reasons.…”
Section: Why Use Gp In Modeling Water Flows?mentioning
confidence: 79%
“…However if the technique is to stay here it needs to be explored further for more challenging problems like modeling of infiltration, high flood events, hurricane path, storm surge, tsunami water levels to name a few. [13] …”
Section: Concluding Remarks and Future Scopementioning
confidence: 99%
“…Previously, short-term estimation and forecast of catchment water yield were based on a range of methods, from purely empirical simple models to highly sophisticated distributed process-based models defined by partial differential equations (e.g., the Systeme Hydrologique Europeen model [11] or the Macaque model [9]). Over the past decades, data-driven models have become increasingly useful in hydrological forecasting on the basis that they avoid having to address the problems of the spatial and temporal variability, and the uncertainty of the inputs and the parameters, as opposed to the physically-based models that require a wide range of catchment and climate information [12][13][14].…”
Section: Introductionmentioning
confidence: 99%